2021
DOI: 10.21203/rs.3.rs-465737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome-wide association study identifies novel susceptibility genes contributing to hearing impairment 

Abstract: Hearing impairment (HI) is a growing public health issue of global concern, which may lead to decreased work efficiency, social withdrawal and depression. However, the knowledge of the genetic basis of HI is limited. We conducted a transcriptome-wide association study (TWAS) on risk of HI by combining an European cohort (578 cases and 583 controls) with a Chinese cohort (89 cases and 209 controls). We identified that 46 genes show transcriptome-wide significant associations with the HI risk in the meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It was also identified that metabolites that showed a significant difference in accumulation between microtia and healthy ear cartilage were associated with Pantothenate and CoA biosynthesis, so these may have an association with the development of microtia ear cartilage ( Yang and He, 2020 ). Finally, with regard to Glycerophospholipid metabolism, this has potential protective roles in the cochlea, which was reported to be significantly related to noise-induced hearing loss ( Xie et al, 2021 ). Taken together, our results indicated that different metabolic processes presenting in the cochleae of R. sinicus and V. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…It was also identified that metabolites that showed a significant difference in accumulation between microtia and healthy ear cartilage were associated with Pantothenate and CoA biosynthesis, so these may have an association with the development of microtia ear cartilage ( Yang and He, 2020 ). Finally, with regard to Glycerophospholipid metabolism, this has potential protective roles in the cochlea, which was reported to be significantly related to noise-induced hearing loss ( Xie et al, 2021 ). Taken together, our results indicated that different metabolic processes presenting in the cochleae of R. sinicus and V. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome-wide association study (TWAS) is a powerful tool to investigate the association between gene expression and traits ( Civelek and Lusis, 2014 ; Wainberg et al, 2019 ). Novel susceptibility genes contributing to hearing impairment were identified with this approach ( Xie et al, 2021 ). TWAS relies on the large-scale transcriptomic analysis from a genetic reference population (GRP).…”
Section: Introductionmentioning
confidence: 99%